Methodology for integrated analysis of vector- and spectroscopic bioimpedance methods - Bello José Luis García; Lafargue Alcibiades Lara; Ciria Héctor Camué; Luna Taira Batista; Leyva Yohandys Zulueta (Journal of Electrical Bioimpedance)
Electrical bioimpedance is based on the opposition exerted by body tissues to the passage of an electrical current. This characteristic allows the assessment of the individual's body composition, nutritional status, and hydration status. Electrical bioimpedance can be used to estimate body composition, health-related markers, general health status, diagnosis and prognostic of diseases, evaluation of treatment progress, and others. The aim of this study is to propose a methodology that allows us to integrate two methods of electrical bioimpedance analysis: bioelectrical impedance vector analysis, and bioelectrical impedance spectroscopy to evaluate the health of individuals.